2019
DOI: 10.3390/agronomy9120775
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Nitrogen Use in Maize

Abstract: Nitrogen (N) fertilizers are needed to enhance maize (Zea mays L.) production. Maize plays a major role in the livestock industry, biofuels, and human nutrition. Globally, less than one-half of applied N is recovered by maize. Although the application of N fertilizer can improve maize yield, excess N application due to low knowledge of the mechanisms of nitrogen use efficiency (NUE) poses serious threats to environmental sustainability. Increased environmental consciousness and an ever-increasing human populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 155 publications
(184 reference statements)
3
50
0
3
Order By: Relevance
“…This phenomenon suggested that N and the factors other than N should be equally focused on for maize production under present management conditions. This index of NHI was believed to reflect the crop NUE, and greater NHI in our case demonstrated there was enhanced NUE for maize with increased use of straw (Cheng et al 2007, Asibi et al 2019). Generally, viewpoint-based on one growing season study emphasised that higher crop NUE in straw addition treatment could be attributed to the N immobilisation-mineralisation process, and this process reduced the unnecessary loss of the non-straw-derived N from N fertiliser (Cao et al 2018) whether the N originating from straw exerted a role over long-term period needed further exploration (see next section).…”
Section: Plant Soil and Environmentmentioning
confidence: 68%
See 1 more Smart Citation
“…This phenomenon suggested that N and the factors other than N should be equally focused on for maize production under present management conditions. This index of NHI was believed to reflect the crop NUE, and greater NHI in our case demonstrated there was enhanced NUE for maize with increased use of straw (Cheng et al 2007, Asibi et al 2019). Generally, viewpoint-based on one growing season study emphasised that higher crop NUE in straw addition treatment could be attributed to the N immobilisation-mineralisation process, and this process reduced the unnecessary loss of the non-straw-derived N from N fertiliser (Cao et al 2018) whether the N originating from straw exerted a role over long-term period needed further exploration (see next section).…”
Section: Plant Soil and Environmentmentioning
confidence: 68%
“…From the crop perspective, the nitrogen harvest index (NHI) could reflect crop N use strategy and NUE (Cheng et al 2007). However, mechanisms underlying the relative contribution of added straw N to increased NUE needed to be explored (Xu et al 2020); how NHI was changed after the straw amendment was also under debate (Asibi et al 2019).…”
mentioning
confidence: 99%
“…Emphasis of the soil nutrient analysis was on nitrogen since it is the limiting nutrient for growth of maize in the experiment location [17]. Nitrogen has been reported as the key determinant nutrient for maize grain yields [22]. The economically optimal nitrogen application rate for maize fields in this part of central Uganda is 50 kg N ha −1 as suggested by Kaizzi et al [23].…”
Section: Study Sitementioning
confidence: 99%
“…Nitrogen is typically the most limiting nutrient for the production of cereal crops [30], but the recovery of applied N in harvested grain is only about 35% of the amount applied worldwide [31], rendering the excess N susceptible to loss, which can lead to environmental degradation [32,33]. To advance N use efficiency in maize production through improved synchrony between N supply and crop N requirements, the review by Asibi et al [34] summarizes recent research and provides new understanding on N assimilation, utilization, and remobilization in maize.…”
Section: Nitrogen Managementmentioning
confidence: 99%